Tracing the translator’s voice: A corpus-based study of six English translations of Daxue - Wang, Huiping (Frontiers in Psychology, 2023)
The Translator’s voice is the “second” voice in a translated narrative. By tracing a set of textual cues, the translator’s voice embedded in the discourse may come to light. This study is based on a self-constructed bilingual parallel corpus which adopts both quantitative and qualitative methods to reveal the translator’s voice in six English versions of the Chinese classic Daxue. Wordsmith 8.0, CLAWS POS Tagger, and Readability Analyzer were used to analyze the data and investigate and compare the lexical, syntactic, and textual features of the translations of Daxue by David Collie, James Legge, Ku Hungming, Ezra Pound, Chan Wing-Tsit, and Andrew Plaks, respectively. Paratexts of translation－prefaces, introductions, translator’s notes, footnotes and so on, as well as representative examples, were also analyzed by close reading. This study attempts to discover the individual translator’s voice within the translated texts of Daxue, and more importantly, to uncover the different sociocultural, historical, and ideological contexts on which they are based. The findings suggest that each translator’s cultural identity, historical background, and motives for producing the translation are made manifest through various linguistic and non-linguistic choices. This study demonstrates that the translator’s voice, which is always present along with the author’s voice and may take various forms, is deeply associated with the cultural and ideological constructs in which the act of translation is embedded. It is hoped that the results of this research will contribute to an enhanced understanding of the translation and overseas dissemination of the Chinese classic Daxue, and further the study of the translator’s voice with the aid of corpus technology.